The Impact of Work Pressures on the Health and Well-being of Healthcare Workers - Ali Hassan Ali Otaifi; Hanan mousa mafia; Itimad Hassan Ali Muawwadh; Mohammed abdu deifallah sharji; Mhammed Ibrahim Ahmed Duraibi; Ibtihaj Hamoud Mohammed Nams; Nora Hamoud Mohammed Nams; Faygh Yahya Hassan Albahri; Zahra Yahya Mohammed Barut; Layla Yehya Ahmad Hatani; Khadijah Nashi Ibrahim Almahawra; Hind mohammed Awidi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Work pressures in the healthcare sector have attracted attention as mobilization activity and protest over them grow. At the heart of this is the well-being of workers, regarded as being under threat in the face of increased service demands and high work intensity. The scarce existing literature on these seemingly different sectors and levels of healthcare identifies health outcomes such as more accidents, increased stress, anxiety, and poorer mental health. The arguments often seem to be based on the assumption that higher levels of work pressure are bad for our performance because workers who are more stressed are less productive and more prone to errors. The NHS does not just want a strong workforce so that health services can be delivered at the lowest cost and without harming patients or users of the system. Rather, the goal is to foster staff health and well-being in itself; as a good in itself rather than just an instrumental means to economic ends. These twin effects of work pressures are visible in rising levels of sickness absence, high employee turnover, a number of complaints, and a declining service to patients. As flimsy a handle as we have for these supposedly intuitive and often asserted claims, we are ill-informed about the exact nature of work pressures and the pressures they may exert.